The Analysis of South Korean Gastrodiplomacy Towards the Increases of South Korean Kimchi Export - Arina Nihayati; Elyana Ade Pertiwi; Tri Inov Haripa (Journal of World Trade Studies, 2021)
This research aims to provide the blueprint of how South Korea both state actors and nonstate actors involved in South Korea’s Gastrodiplomacy. This research will provide the details of South Korea government implementation of “Kimchi Diplomacy” in the world and the increases of South Korean Kimchi export. This research uses literature studies to collect all the information and data needed to answer Gastrodiplomacy impact on the South Korean economy. Gastrodiplomacy is a form of South Korea's soft power in promoting culinary culture, especially Kimchi. South Korea's strategy in introducing the world to their Kimchi commodity tends to be carried by people to people. In addition, Gastrodiplomacy is used by the South Korean government as a national branding to the world. This strategy has succeeded in improving the country's economic situation, especially the increase in exports of South Korean Kimchi commodities. South Korea's Kimchi exports have increased since 2011 and reached a tipping point to 144.51 million USD in 2020. This study indicates a relationship between South Korea's Gastrodiplomacy strategy and the improvement of the Kimchi commodity economy.